An evaluation of the effectiveness of the R time intervention and the circle time intervention in promoting children‘s emotional literacy and mental well-being - Sedgwick, Lynne (2013)
This research study evaluated the effectiveness of the R time intervention and the Circle Time intervention to promote year 2/3 children‘s emotional literacy and mental well-being. Theoretical perspectives of emotional literacy and the related broader concept of mental well-being provided a framework to evaluate the development of a wide range of social and emotional skills and behaviours (Goleman‘s, 1996, 1998; Mayer & Salovey, 1997). The emphasis on developing child well-being in UK government agendas (e.g. DfEE, 2001) and intervention research (e.g. Weare & Gray, 2002; Adi, Killoran, Janmohamed, & Stewart-Brown, 2007), made the study of whole class interventions such as R time and Circle Time a relevant area of study. In three schools, the class teacher delivered the R time intervention (n=25), the Circle Time intervention (n=14) and normal practice (n=16) over 8 weeks to year 2/3 children. The Emotional Literacy Assessment Instrument (ELAI) and the Strengths and Difficulties Questionnaire (SDQ) measured pre- to post-test change in teacher, parent and pupil informant scores. A Multivariate Analysis of Variance (MANOVA) showed Circle Time self-awareness scores and R time and Circle Time pro-social behaviour scores significantly increased following the intervention. The results suggest Circle Time had significant positive effects on children‘s self-awareness compared to R time. The discussion considered the session length and duration of the interventions as possible threats to internal validity of the study. Future studies might investigate the effectiveness of the interventions implemented over a longer period and if positive gains remain at a follow up. This study suggests EPs have a role in supporting schools to implement, design and evaluate interventions in this area. In conclusion, the results of the study suggest R time effectively promoted an aspect of children‘s mental well-being (pro-social behaviour) and Circle Time effectively promoted an aspect of children‘s emotional literacy skills (self-awareness) and mental well-being (pro-social behaviour).